Verbesina encelioides: A Fast Spreading Weed in Semi-arid Regions of North-Western India. Is Climate Change Responsible? - Mehal, K. K. (Journal of Scientific Research, 2021)
Alterations in rainfall pattern and rise in temperature along with various anthropogenic disturbances are contributing greatly to biological invasion. In response to ongoing climate change, the sub-tropical and semi-arid regions are shifting towards dry deserts and arid regions, which create a propitious chance for the establishment of highly efficient and opportunistic invasive plant species at the cost of native vegetation. Verbesina encelioides is one of such exploitative plants spreading fast in many semi-arid as well as arid regions of the world. Although the presence of V. encelioides dates back to 1960s, but its emergence as a dominant invasive weed of dry areas is recent in India. The present study focused on the rapid spread of V. encelioides in the north-western states of India owing to its ecological traits as well as changing climate patterns of the country.